2nd International Conference on Testbeds and Research Infrastructures for the Development of Networks and Communities, 2006. TR 2006
DOI: 10.1109/tridnt.2006.1649150
|View full text |Cite
|
Sign up to set email alerts
|

Frame-based modeling of H.264 constrained videoconference traffic over an IP commercial platform

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Summing up the above analysis, it is evident that the Gamma density is better for H.261 unconstrained traffic, the Loglogistic for unconstrained H.263, H.263+ traffic, and the C-LVMAX method for all cases of constrained traffic (including H.264 traffic, as proposed in [32]). However, if a generic and simple model needed to be applied for all cases then the most dominant would be the Loglogistic density.…”
Section: Fitting Of the Frame-size Frequency Histograms Of The Tracesmentioning
confidence: 84%
See 1 more Smart Citation
“…Summing up the above analysis, it is evident that the Gamma density is better for H.261 unconstrained traffic, the Loglogistic for unconstrained H.263, H.263+ traffic, and the C-LVMAX method for all cases of constrained traffic (including H.264 traffic, as proposed in [32]). However, if a generic and simple model needed to be applied for all cases then the most dominant would be the Loglogistic density.…”
Section: Fitting Of the Frame-size Frequency Histograms Of The Tracesmentioning
confidence: 84%
“…�peci�cally, as shown in [32] for the H.264 traffic, it can be characterized as constrained and the generated traffic is uncorrelated and can be accurately represented by a queue.…”
Section: Traffic Analysis and Modelling Assessmentmentioning
confidence: 99%
“…3 is the proportions of large (4512 bytes) and small (o512 bytes) packet sizes in the video streams. Video codec traffic modeling studies such as Kouremenos et al (2006) and Domoxoudis et al (2006) have also demonstrated comparable proportions of large and small packet sizes in the video streams generated by video codecs such as H.261, H.262, H.263 and H.264 found in popular desktop videoconferencing end-points.…”
Section: Bandwidthmentioning
confidence: 91%